KOMPARASI ESTETIK BATIK FRAKTAL DENGAN BATIK NUSANTARA TRADISI - Andri Nur Cahyo; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2022)
ABSTRACT Batik fractal is a modern batik made refer to the tradition motif combined with fractal visual in computational way. As an innovation in the arena batik Nusantara, batik fractal managed to integrate the digital technology with fractal visuality as a major milestone work design. It has produced a form of batik modern that play an important role in bringing batik Nusantara to face the global competition. This journal will discuss the relationship between batik fractal with batik tradition in the constellation batik Nusantara through the aesthetic comparative study. Keyword: Batik Fractal, Batik Nusantara, Comparative Study.